Penerapan Manajemen Strategi Dalam Dakwah Nabi Muhammad Shallallahu ‘Alaihi Wa Sallam - Muhammad Fachran Haikal; Cindy Suci Aisyah Simarmata; Hany Tasya Luthfiah (Universitas Pahlawan Tuanku Tambusai, 2023)
The management of the da'wah strategy carried out by Prophet Muhammad Shallallahu 'Alaihi Wa Sallam is guided by the most important book, namely the Qur'an which teaches how important it is to do amar ma'ruf and nahi munkar by paying attention to segmentation and the needs of the object of da'wah. Prophet Muhammad Shallallahu 'Alaihi Wa Sallam used various da'wah tactics. In formulating his strategy or political preaching, Prophet Muhammad Shallallahu 'Alaihi Wa Sallam always paid attention to the condition of his object, social background, degree of education and ability, as well as his economic position. This shows that of course every preaching he does is always neatly arranged, full of consideration and planning, as well as organized and controlled. In other words, the da'wah of the Prophet is a da'wah whose management strategy is very good. This article attempts to describe how the strategic management was implemented by Prophet Muhammad Shallallahu 'Alaihi Wa Sallam, especially in his preaching so that now Islam is spread throughout the universe.